Change Phenomena of Spatial Physical in the Dynamics of Development in Urban Fringe Area - Batara Surya (Indonesian Journal of Geography, 2016)
Abstract The study aims at analyzing change of spatial physical, spatial articulation, spatial structure, social and agglomeration and deagglomeration of function in the dynamics of development in the fringe area of Hertasning-Samata, Makassar City. Spatial physical changes are designated by the presence of new socio-economic functions that drive spatial structure changes, spatial articulation, social changes and agglomeration/deagglomeration of function in the fringe area of Hertasning-Samata. It applies quantitative and qualitative approaches (mixed method). Data is acquired from some sources and community informants living in the fringe area of Hertasning-Samata, Makassar City. Rapid and revolutionary spatial physical changes contribute positively to spatial structure changes, spatial pattern, agglomeration/ deagglomeration of area function. Spatial function change which had been dominated by commercial function becomes the determinant of social changes in the fringe area of Hertasning-Samata. Domination of mastery of reproduction of space by capitalism shows differences in mastery of reproduction of space significantly between space of capitalism and space of pre-capitalism. It sharpens economic stratum, status differences, between space of capitalism and space of pre-capitalism and socio-community classes. The dynamic of spatial physical change causes orientation shift to community activity which had run along dialetic of modernity and rationalization of action in local community.Abstrak Penelitian ini bertujuan untuk menganalisis perubahan fisik spasial, artikulasi spasial, perubahan struktur ruang, perubahan sosial, aglomerasi fungsi dan dis-aglomerasi fungsi dalam dinamika pembangunan kawasan pinggiran Hertasning-Samata Kota Makassar. Perubahan fisik spasial ditandai dengan keberadaan fungsi-fungsi kegiatan sosial-ekonomi baru, mengondisikan perubahan struktur ruang, artikulasi spasial, perubahan sosial dan aglomerasi/dis-aglomerasi fungsi kawasan pinggiran Hertasning-Samata. Penelitian ini menggunakan pendekatan kuantitatif dan kualitatif (mixed method). Data diperoleh dari beberapa sumber dan informan komunitas yang mendiami kawasan pinggiran Hertasning-Samata Kota Makassar. Perubahan fisik spasial yang sangat cepat dan revolusioner berkonstribusi positif terhadap perubahan struktur ruang, pola ruang, aglomerasi/dis-aglomerasi fungsi kawasan. Perubahan fungsi ruang yang didominasi fungsi komersil menjadi determinan perubahan sosial pada kawasan pinggiran Hertasning-Samata. Dominasi penguasaan reproduksi ruang oleh kapitalisme menunjukkan perbedaan penguasaan reproduksi ruang yang sangat signifikan antara ruang kapitalisme dan ruang prakapitalisme, berdampak pada penajaman strata secara ekonomi, perbedaan status, dan kelas-kelas sosial komunitas. Dinamika perubahan fisik spasial menyebabkan pergeseran orientasi kegiatan komunitas yang berjalan sejajar dengan dialektika modernitas dan rasionalisasi tindakan dalam komunitas lokal.